help plz solve this question
Attachments:
![](https://hi-static.z-dn.net/files/dcd/abacf8bc6364bd4caf3422b28f8120fa.jpg)
Answers
Answered by
0
Hey Mate
your answer is ---
Given, sides of a triangle are m^2-n^2 and 2mn
so, by Pythagoras theorem
hypotenuse = (m^2-n^2)^2 + (2mn)^2
= m^4+n^2-2m^2n^2 +4m^2n^2
= m^4+n^4 +2m^2n^2
so, hypotenuse = (m^2+n^2)^2
hope it helps you
your answer is ---
Given, sides of a triangle are m^2-n^2 and 2mn
so, by Pythagoras theorem
hypotenuse = (m^2-n^2)^2 + (2mn)^2
= m^4+n^2-2m^2n^2 +4m^2n^2
= m^4+n^4 +2m^2n^2
so, hypotenuse = (m^2+n^2)^2
hope it helps you
Similar questions